Heaven - Johnson, Angela, 1961- (New York : Simon & Schuster Books for Young Readers, 1998)
Fourteen-year-old Marley's seemingly perfect life in the small town of Heaven is disrupted when she discovers that her father and mother are not her real parents.
G5
Keywords: Adoption -- Fiction; Parent and child -- Fiction; African Americans -- Fiction